INTERNAL DERANGEMENTS OF THE TMJ: AN UPDATE - Molina, Omar Franklin Tinoco (REVISTA CEREUS, 2010)
Objectives: To review the literature on internal derangements of the temporomandibular joint and describe the characteristics of common TMJ internal derangements. Material and methods: A monograph and additional papers on TMJ-internal derangements were used to prepare this study. A total of 39 papers were evaluated summarizing major aspects of each study. Results: A total of 8 internal derangements including capsulitis, retrodiscal pain, disk attachment pain, disk displacement without reduction, arthralgia, osteoarthritis, osteoarthrosis and synovial chondromatosis are commonly described in the literature. Some of these disorders may be diagnosed clinically. However, more complex disorders including arthralgia, disk displacement without reduction and synovial chondromatosis need more sophisticated methods to obtain an accurate diagnosis. Conclusions: 1. There are more than 8 internal derangements of the temporomandibular joints presenting with different clinical, epidemiological and diagnostic characteristics. 2. Diagnosis of such categories is carried using history and description of sign and symptoms, magnetic resonance and tomographic images and more sophisticated methods. 3. The treatment of such disorders include splints, counseling, drugs, self care, warm, physiotherapy, TENS, local anesthetics and even surgery.